Comparison of two doses of succinylcholine to facilitate the Laryngeal mask airway insertion under propofol anaesthesia in adult patients undergoing elective minor surgical procedures - Gunaseelan, S; Prabu, R Krishna (Asian Journal of Medical Sciences, 2017)
Background: Small dose of succinylcholine combined with propofol facilitates Laryngeal mask airway (LMA) insertion. This study was designed to compare the efficacy of two different small doses of succinylcholine for LMA insertion. Aims and Objectives: The aim of our study is to compare the usefulness of two different doses of succinylcholine to facilitate the insertion of laryngeal mask airway under intravenous anaesthesia. Material and Methods: 70 patients of ASA I and II posted for elective day care procedure under general anaesthesia with Laryngeal mask airway (LMA) were randomly allocated into two groups of 35 each. 35 patients in group PS1 received Inj. propofol 2.0 mg/kg + succinylcholine 0.1 mg/kg (diluted to 2 ml). 35 patients in group PS2 received Inj. propofol 2.0 ml/kg + succinylcholine 0.2 mg/kg (diluted to 2 ml). During insertion of laryngeal mask airway jaw relaxation, gagging/coughing, head and limb movements, presence or absence of laryngospasm and duration of apnoea were noted. Results: Patients in PS2 had better conditions for LMA insertion, reduced the upper airway responses to the LMA insertion, and reduced the supplement doses of propofol compared to PS1. Conclusion: Succinylcholine in 0.2 mg/kg compared to 0.1kg provides optimal conditions for LMA insertion. Asian Journal of Medical Sciences Vol.8(4) 2017 21-26